The Influence of Independent Commisioners Managerial Ownership Green Accounting on Financial Performance - Nazhila, Irma Putri; Amin, Muhammad Nuryatno (PT Mattawang Mediatama Solution, 2024)
The aim of this research is to determine the influence of independent commissioners on managerial ownership of green accounting on the financial performance of consumen non-cyclicals sectors companies. This type of research is quantitative. The data sources used are primary data and secondary data. Primary data was obtained from questionnaires. Secondary data from company data, journals and books. Independent commissioners positively impact financial performance. Through objective and independent oversight, companies can enhance financial performance via more effective management, increased transparency, and greater investor confidence. Managerial ownership also significantly improves financial performance. When management holds company shares, they have a strong incentive to encourage financial performance, minimize conflicts of interest, and make more strategic decisions. Similarly, green accounting has a notable positive effect on financial performance.